Protective effect and mechanism of action of diallyl disulfide against acetaminophen-induced acute hepatotoxicity. (November 2017) - Ko, Je-Won; Park, Sung-Hyeuk; Shin, Na-Rae; Shin, Jin-Young; Kim, Jeong-Won; Shin, In-Sik; Moon, Changjong; Heo, Jeong-Doo; Kim, Jong-Choon; Lee, In-Chul
Abstract: The aim of this study was to investigate the potential protective effects of diallyl disulfide (DADS) against acetaminophen (AAP)-induced acute hepatotoxicity and elucidate the molecular mechanisms underlying these protective effects in rats. Treatment with AAP caused acute hepatotoxicity manifested by elevated levels of aspartate aminotransferase and alanine aminotransferase with corresponding histopathological changes and high levels of oxidative stress in the livers. AAP treatment also caused hepatocellular apoptosis with phosphorylation of c-Jun-N-terminal protein kinase (JNK). In addition, AAP caused activation of nuclear factor kappaB (NF-κB) concurrent with induction of inflammatory mediators. In contrast, pretreatment with DADS effectively attenuated acute liver injury and oxidative stress caused by AAP. DADS pretreatment suppressed cytochrome P450 2E1 (CYP2E1) levels in a dose-dependent manner and inhibited elevation of CYP2E1 activity induced by AAP. DADS pretreatment suppressed the phosphorylation of JNK and attenuated hepatocellular apoptotic changes. In addition, DADS inhibited the nuclear translocation of NF-κB and subsequent induction of inflammatory mediators. Overall, these results indicate that DADS confers a protective effect against oxidative stress-mediated JNK activation and apoptotic changes caused by AAP in the rat livers. This may be due to its ability to inhibit CYP2E1, enhance antioxidant enzymes activities, and suppress NF-κB activation. Highlights: Diallyl disulfide (DADS) attenuated oxidative hepatotoxicity induced by acetaminophen (AAP). DADS inhibited elevation of CYP2E1 activity induced by AAP. DADS suppressed the phosphorylation of JNK and attenuated hepatocellular apoptotic changes. DADS inhibited inflammatory responses by inhibiting NF-κB activation.